Three-quarters of species’ ranges have not been covered by protected areas in global borders - Wenjie Li; Qing Zhang; Zhining Wang; Xuan Liu (Nature Communications)
Abstract Borderlands are increasingly recognized as critically important for biodiversity conservation owing to their ecological significance and high political profile. However, the species ranges covered by protected areas and their influencing factors in transboundary areas are still largely unknown worldwide. Here, based on the distributional ranges of 19,039 terrestrial vertebrates, we find that three-quarters of species’ ranges in global borders remain uncovered by protected areas, particularly in tropical areas of Southeast Asia and West Africa. The average protected area coverage of species ranges is lower in transboundary areas than non-transboundary areas after accounting for geographical differences in sampling efforts. We also observe that protected area coverage of species ranges increases with governance effectiveness, collaboration abilities, protection levels, sizes and establishment years of protected areas, and topographic complexity, but decreases with human population density, human development index, and cropland expansion. Furthermore, protected areas simultaneously face threats of ongoing global challenges from climate change, land-use modification, and alien species invasion, and the proportions of borderlands threatened by global changes are higher than elsewhere. All these findings demonstrate that cross-border cooperation is urgently needed to achieve the ambitious goal of global biodiversity conservation by 2050.